Hubungan Pengetahuan, Dukungan Suami, dan Lingkungan terhadap Pemberian Imunisasi DPT pada Bayi - Santi, Santi; Sugesti, Retno; Karubuy, Milka Anggraeni (MPI Press, 2024)
Introduction: The ministry of health of the Republic of Indonesia recorded a drastic decrease in immunization achievement in the last 2 years (2020 – 2021). In 2020, the immunization target is 92%, while the coverage achieved is only 84%, and likewise in 2021, immunization is targeted at 93%, but the coverage achieved is only 84%. The drastic decrease was confirmed through data at the sub-district level, namely the Klapanunggal Health Center, which showed DPT-HB-HIB1 3 coverage of 64.2% of the target of 95% in 2021. Objectives: To find out the relationship between knowledge, husband's support, and the environment towards giving DPT immunization to babies at PMB FDN in Klapanunggal District, Bogor in 2022. Method: This type of research is analytical and descriptive with a cross-sectional design. The types of data used in this study are secondary data and primary data. The population in this study was 100 people, then the sampling method used the purposive method so that the total sample was 50 people. Data collection techniques using questionnaires. Data analysis in this study used univariate analysis and bivariate analysis with chi-square test. Result: The relationship between knowledge and DPT immunization was obtained with a p-value of 0.0 with OR = 50 (95% CI = 5,700-438,569). The relationship between the husband's support and DPT immunization was obtained with a p-value of 0.04 and OR = 7.719 (95% CI = 1.720-29.975). The relationship between environment and DPT immunization was OR = 7.719 (95% CI = 1.720-29.975). Conclusion: There is a relationship between knowledge, husband's support, and the environment with the provision of DPT immunization at PMB FDN Klapanunggal.